Substansial Kepuasan Konsumen Rumah Makan “Soto Dok Lamongan” Nganjuk - Ratnanto, Sigit Ratnanto; Purnomo, Hery (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study is to find out how the signification of taste, store atmosphere and price affects the consumer satisfaction of Rumah Makan